Activity pattern of Viverridae in state land forest, Merapoh, Pahang - Adanan, Nurul Izzati (2020)
A series of camera trapping surveys were conducted to observe the activity pattern of Viverridae in State Land Forest, Merapoh, Pahang. A total of 13 camera traps were deployed at study sites, continuously for two months from end of August 2019 until end of October 2019. A total 14 number of independent photo in family Viverridae from 4 species were detected in the study. Large Indian Civet was the most species founded where 10 of the total independent photo were captured by camera traps, Common Palm Civet with 2 images while Banded Linsang and Otter Civet with 1 independent photo only. Camera trap data on activity patterns shown that Large Indian Civet (Viverra zibetha), Common Palm Civet (Paradoxurus hermaphrodites), Banded Linsang (Prionodon linsang) and Otter Civet (Cynogale bennetti) are nocturnal animals since it happened during the night. This defined separation among the Viverridae assemblage for the State Land Forest, Merapoh suggests a probable relationship with resource distribution at the ecosystem level (prey and foraging competition). The basic knowledge thus gained shows the importance of recording and analysing data on tropical rainforest Viverridae community ecology from camera-trap studies.